Jovian Planets and Lunar Nodal Cycles in the Earth’s Climate Variability - Yndestad, Harald (Frontiers in Astronomy and Space Sciences, 2022)
The origin of Earth’s climate variability is poorly understood. This study is based on a Jovian planet (Jupiter, Saturn, Uranus, Neptune) variability model (JSUN). The JSUN model is transformed into a Total Solar Irradiation (TSI) variability model and a Sea Surface Temperature (SST) variability model. The JSUN model computes TSI minima when JSUN periods have a perihelion phase that coincides in periods of [170, 500, 999, 1961, 2451, 4450] years. The JSUN variability is confirmed by period- and phase-coincidences to solar position oscillation and TSI (ACRIM-HS) data series. The TSI model reveals a direct relation between JSUN perihelion coincidences and deep solar minima from 1000 AD. The TSI-forced SST model introduces JSUN phase shifts and new 4450-year envelope periods of minima and maxima. The lunar nodal cycle model computes lunar-forced SST periods up to 446 years. Jovian planets and lunar nodal cycles in Earth’s climate variability are constructive and destructive interferences between a JSUN forced SST period spectrum and a lunar nodal forced SST period spectrum. The solar-lunar-forced SST variability is confirmed by a wavelet spectrum analysis of Earth’s climate data series (HadCRUT4, HadSST3, CRUTEM4, GISP2). The study confirms constructive and destructive interference between solar-forced and lunar-forced SST periods, up to 4450 years. Lunar-forced SST periods coincide with climate periods. Solar-forced SST periods coincide with climate amplitude variations. The time-variant interference between solar-forced and lunar-forced climate periods is never repeated. Upcoming events may still be deterministic because JSUN periods and lunar nodal periods are deterministic. Climate variations (GISP2), in what is known as the “Little Ice Age”, reveal cold and warm periods in a total period of 1000 years from 1193 to 2193 A.D.